Plasma membrane-localized SEM1 protein mediates sugar movement to sink rice tissues - Wang, Yanwei; Sun, Jing; Deng, Chen; Teng, Shouzhen; Chen, Guoxin; Chen, Zhenhua; Cui, Xuean; Brutnell, Thomas P.; Han, Xiao; Zhang, Zhiguo; Lu, Tiegang (Wiley, 2022)
The translocation of photosynthate carbohydrates, such as sucrose, is critical for plant growth and crop yield. Previous studies have revealed that sugar transporters, plasmodesmata and sieve plates act as important controllers in sucrose loading into and unloading from phloem in the vascular system. However, other pivotal steps for the regulation of sucrose movement remain largely elusive. In this study, characterization of two starch excesses in mesophyll (sem) mutants and dye and sucrose export assays were performed to provide insights into the regulatory networks that drive source–sink relations in rice. Map‐based cloning identified two allelic mutations in a gene encoding a GLUCAN SYNTHASE‐LIKE (GSL) protein, thus indicating a role for SEM1 in callose biosynthesis. Subcellular localization in rice showed that SEM1 localized to the plasma membrane. In situ expression analysis and GUS staining showed that SEM1 was mainly expressed in vascular phloem cells. Reduced sucrose transport was found in the sem1‐1/1‐2 mutant, which led to excessive starch accumulation in source leaves and inhibited photosynthesis. Paraffin section and transmission electron microscopy experiments revealed that less‐developed vascular cells (VCs) in sem1‐1/1‐2 potentially disturbed sugar movement. Moreover, dye and sugar trafficking experiments revealed that aberrant VC development was the main reason for the pleiotropic phenotype of sem1‐1/1‐2. In total, efficient sucrose loading into the phloem benefits from an optional number of VCs with a large vacuole that could act as a buffer holding tank for sucrose passing from the vascular bundle sheath.